2009
DOI: 10.3928/01477447-20090201-12
|View full text |Cite
|
Sign up to set email alerts
|

Antifibrinolytic Therapy in Complex Spine Surgery: A Case-Control Study Comparing Aprotinin and Tranexamic Acid

Abstract: A case-control study was performed to determine the impact of aprotinin or tranexamic acid use on reducing intraoperative blood loss and transfusion needs in complex spine surgery. Sixty-nine patients undergoing complex spine surgery received aprotinin or tranexamic acid. The aprotinin group contained 30 patients (8 men and 22 women) and the tranexamic acid group 39 patients (11 men and 28 women). The following variables were recorded: duration of surgery, number of levels fused, intraoperative and total blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Therefore the total transfusion rate was 2.6. The authors found that the duration of surgery was the main predictive factor of total blood loss among the patients [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the total transfusion rate was 2.6. The authors found that the duration of surgery was the main predictive factor of total blood loss among the patients [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…ivTXA has also been used for hemostasis in cervical spinal procedures and spinal tumor surgery 63 64 ; several RCTs have demonstrated its beneficial effects in overall complex spinal surgery procedures. 65 66 An RCT conducted by Elwatidy et al involving patients ( n = 64) undergoing different kinds of major, mostly multilevel, spinal surgery used a high-dose protocol (2 g loading dose for adults or 30 mg/kg for children, followed by a maintenance dose of 100 mg/h for adults or 1 mg/kg/h for children) of ivTXA, which was continuously administered up to 5 hours after the surgery. 65 Total blood loss in the treatment group was reduced by almost half, with a 48% reduction intraoperatively and 55% reduction in postoperative drain output.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies reported detailed information regarding the randomization techniques that were used, such as manual random number selection or computer-generated random number table; Xu et al [20] did not specify a randomization method. Allocation concealment was high in 4 studies [1,2,20,21] and low in the others. The studies by Taghaddomi et al [22] and Xu et al [20] were rated as unclear to blinding of the participants and the outcome assessor.…”
Section: Quality Assessment For Included Studies (Risk Of Bias Within Studies)mentioning
confidence: 90%